O gênero Zygostates (Orchidaceae: Oncidiinae) no estado do Paraná, Brasil - Royer, Carla Adriane [UNESP]; Toscano De Brito, A. L.V.; De Camargo Smidt, Eric (FapUNIFESP (SciELO), 2017)
Zygostates comprises ca. 26 species of which 15 occur in Brazil. Based on fieldwork and study of Brazilian and foreign herbaria eight species of Zygostates are recognized for Paraná: Zygostates alleniana, Z. bradei, Z. cornuta, Z. dasyrhiza, Z. lunata, Z. multiflora, Z. pellucida and Z. pustulata. The genus is recorded for 36 out of 399 municipalities, mostly inhabiting areas of Floresta Ombrófila Densa and Floresta Ombrófila Mista in Serra do Mar, Primeiro and Segundo Planaltos. Zygostates alleniana has low extinction risk according to IUCN criteria since it is distributed all over the state, while Z. bradei, Z. pellucida and Z. multiflora are found in only one locality, and, thus, they are the most threatened species. Zygostates bradei is Possibly Extinct locally; Z. pellucida and Z. multiflora are Critically Endangered. A key for species identification, descriptions, illustrations, list of specimens examined, distribution maps and conservation status for all taxa are herein provided.
The genus Zygostates (Orchidaceae: Oncidiinae) in the state of Paraná, Brazil
Keywords: Atlantic Forest; Biodiversity; IUCN; Paraná flora